THE ROLE OF PEDAGOGICAL METHODS IN THE FORMATION OF THE CONCEPT OF ETHNO-CULTURAL TOLERANCE IN STUDENTS - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
The methodology of ethno-cultural tolerance in the descriptive plan is considered by the authors of the article at four levels: philosophical, general scientific, concrete-scientific, methodical (technological). Each of them is presented in many aspects, as a result of which the reader has a holistic view of the large-scale theoretical resource for the formation of ethno-cultural tolerance, its wide problem field. A systematic vision of this process allows us to draw conclusions about the consistent increase in the methodological potential of ethnocultural tolerance, the methodological shift from aspectual analysis to the formulation of concepts and ideas, and the increase in the methodological culture of specialists in this field.
Keywords: methodology; ethnic; cultural tolerance